Identification of Whole-Genome Significant Single Nucleotide Polymorphisms in Candidate Genes Associated With Serum Biochemical Traits in Chinese Holstein Cattle - Shi, Kerong; Niu, Fugui; Zhang, Qin; Ning, Chao; Yue, Shujian; Hu, Chengzhang; Xu, Zhongjin; Wang, Shengxuan; Li, Ranran; Hou, Qiuling; Wang, Zhonghua (Frontiers in Genetics, 2020)
A genome-wide association study (GWAS) was conducted on 23 serum biochemical traits in Chinese Holstein. The experimental population consisted of 399 cattle, each genotyped by a commercial bovine 50K SNP chip, which had 49,663 SNPs, After data cleaning, 41,092 SNPs from 361 Holstein were retained for GWAS. The phenotypes were measured values of serum measurements of these animals, taken at 11 days after parturition. Two statistical models, a fixed-effect linear regression model (FLM) and a mixed-effect linear model (MLM), were used to estimate the association effects of SNPs. Genome-wide significant and suggestive thresholds were set up to be 1.22E-06 and 2.43E-06, respectively. In Chinese Holstein population, FLM identified 81 genome-wide significant (0.05/41,092 = 1.22E-06) SNPs associated with 11 serum traits. Among these SNPs, 5 SNPs (BovineHD0100005950, ARS-BFGL-NGS-115158, BovineHD1500021175, BovineHD0800028900 and BTB-00442438) were also identified by the MLM to have genome-wide suggestive effects on CHE, DBIL, and LDL, respectively Both statistical models pinpointed two SNPs, which had significant effects in Holstein population. The SNP BovineHD0800028900 (which locates nearby the gene LOC101903458 on chromosome 8) was identified to be significantly associated with serum high and low-density lipoprotein (HDL and LDL), whereas BovineHD1500021175 (which locates in 73.4Mb on chromosome 15) was significantly associated SNP with total bilirubin and direct bilirubin (TBIL and DBIL). Further analyses are needed to identify the causal mutations affecting serum traits and to investigate the correlation of effects for loci associated with fatty liver disease in dairy cattle.